I Rapporto - Dimensioni, dinamiche e attrattività dell'Istruzione superiore terziaria a Milano e in Lombardia - Bratti, Massimiliano; Lippo, Enrico (Milan Higher Education Observatory - MHEO, 2023)
The Milan Higher Education Observatory (MHEO) has as its object of analysis the tertiary education system (University, AFAM and ITS Academy) of the Metropolitan City of Milan and the Lombardy region. This first report presents the players in the higher education system in the geographical area of interest, addresses the issue of educational offers by providing data on the number and composition by areas of study of the courses offered by the three kinds of institutions, details the composition of students by level of education, by area of study and by gender, and finally addresses the issue of PhDs, by providing data not only on the current situation but also on recent trends.